Simulasi Terbentuknya Gelombang Permukaan Akibat Adanya Longsoran Bawah Laut (Metode Lax- Friedrich) - Yenci Brika Enkekes; Rifky Fauzi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2023)
The problem studied in this paper is the formation of surface waves due to underwater landslides. The shallow water wave equation is employed to study the phenomenon. The equation is solved numerically by using the Lax-Friedrich method. The numerical result show that this method is able to simulate the generation of surface wave due to underwater landslide.